PERSEPSI PETANI TERHADAP PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN PRODUKTIVITAS USAHATANI TOMAT DI DESA LEWOKELENG KECAMATAN ILE BOLENG KABUPATEN FLORES TIMUR - Lamatwelu, Eufransia Sance; Abdurrahman, Mustafa; Kapioru, Charles (Undana Press, 2024)
This research carried out in Lewokeleng Village, Ile Boleng District, Regency East Flores from February to March 2023. This research aims to find out; 1) knowing the role of agricultural extension workers in increasing the productivity of tomato farming in Lewokelenh Village, Ile Boleng District, East Flores Regency, 2) knowing farmer’s perceptions of the role of agricultural extension workers in increasing the productivity of tomato farming in Lewokeleng Village, Ile Boleng District, East Flores Regency. Determination of the location is one of the central areas of horticulture. The population in this study were all tomato farmers in Lewokeleng Village, namely as many as 35 families. All were assigned as samples to determine the second objective. The data were analyzed descriptively using Likert scale. To determine the first objective, the data were analyzed descriptively qualitatively. The results of analysis show that: 1) The role of agricultural extension workers in increasing the productivity of tomato farming in Lewokeleng Village is based on five roles, namely as a communicator, innovator, educator, facilitator, and motivator in order to improve and develop farmer’s insights to make decisions in farming activities,especially farming to matoes. 2) Farmer’s perceptions of the role of agricultural extension works in increasing the productivity of tomato farming in Lewokeleng Village, Ile Boleng District, East Flores Regency are quite satisfactory with an average score of 3,005 with a maximum percentage of achieving a score of 60.1%